2020
DOI: 10.1029/2019jd031488
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Variability of Cloud Fraction From DSCOVR/EPIC Observations

Abstract: The location of the Earth Polychromatic Imaging Camera (EPIC) aboard the Deep Space Climate Observatory (DSCOVR) offers a global view of the Earth and captures its atmosphere at different locations and time of the day. In this paper, we take advantage of that unique feature to study the daytime variability of cloud fraction in a seasonal and zonal context. We observe that the ensemble behavior over ocean has a distinctive convex shape, with higher cloud fractions at early morning and late afternoon, while no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It demonstrates that the instrument is a legitimate source for determining the liquid cloud fraction, capturing persistent low‐clouds regions such as those identified by CloudSat/CALIPSO in the Northeast and Southeast Pacific, Northeast and Southeast Atlantic, Southeast Indian Ocean, North Atlantic, North Pacific and Southern Ocean (Muhlbauer et al., 2014). A comparison between EPIC's seasonal zonally averaged cloud fractions with those obtained by the operational MODIS cloud mask (MOD35) (King et al., 2013) showed that EPIC properly captures the seasonal dependence of liquid cloud fraction (Delgado‐Bonal et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrates that the instrument is a legitimate source for determining the liquid cloud fraction, capturing persistent low‐clouds regions such as those identified by CloudSat/CALIPSO in the Northeast and Southeast Pacific, Northeast and Southeast Atlantic, Southeast Indian Ocean, North Atlantic, North Pacific and Southern Ocean (Muhlbauer et al., 2014). A comparison between EPIC's seasonal zonally averaged cloud fractions with those obtained by the operational MODIS cloud mask (MOD35) (King et al., 2013) showed that EPIC properly captures the seasonal dependence of liquid cloud fraction (Delgado‐Bonal et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…EPIC cloud products have been previously used to quantify daytime variability for specific regions with well‐known daytime cycles of marine stratocumulus and convective clouds (Delgado‐Bonal et al., 2020). Here we aim to focus on the daytime cloud fraction variability for the entire globe.…”
Section: Resultsmentioning
confidence: 99%
“…This agreement might be purely coincidental and treated with caution, since the Cumberland Plain site was the least spatially representative site at the EPIC nominal resolution. The actual EPIC measurements used in this study may in fact come even from an area twice as large due to the large oblique angles around the hinge region (Delgado-Bonal et al, 2020). The two sites from Victoria, Whroo and Wombat, were found to be spatially non-representative at the EPIC nominal resolution.…”
Section: Discussionmentioning
confidence: 97%
“…That change mitigated the inability to determine cloud top height/pressure from EPIC. These channels along with other VIS/NIR channels have been used to determine cloud fraction Delgado-Bonal et al, 2020), cloud phase and optical depth (Meyer et al, 2016) and cloud-top height/pressure (Yang et al, 2013Davis et al, 2018a;Yin et al, 2020). An example of the cloud fraction retrieved from EPIC is compared with the higher resolution cloud retrieval composite from Khlopenkov et al (2017) in Figure 8.…”
Section: Surface and Atmospheric Propertiesmentioning
confidence: 99%